2013
DOI: 10.1310/tsr2004-331
|View full text |Cite
|
Sign up to set email alerts
|

Time Course and Influence of Pusher Behavior on Outcome in a Rehabilitation Setting: A Prospective Cohort Study

Abstract: The prevalence of PB and its influence on rehabilitation outcome reveal PB as a relevant disorder in stroke rehabilitation. However, the duration of the behavior differed widely among the PB patients. Further studies are needed to establish prognostic criteria for identifying patients with a potential for developing long-term PB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 16 publications
0
39
0
1
Order By: Relevance
“…patients with pusher syndrome need much longer time to recover motor function, compared to patients without pusher syndrome. 18 therefore, earlier diagnosis and treatment of pusher syndrome can effectively facilitate the recovery of mobility and shorten hospitalization time. 19 Studies have reported that visual feedback training, which corrects subjective vertical sense the Canadian Journal of neurologiCal SCienCeS through visual input, is beneficial to control symptoms of pusher syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…patients with pusher syndrome need much longer time to recover motor function, compared to patients without pusher syndrome. 18 therefore, earlier diagnosis and treatment of pusher syndrome can effectively facilitate the recovery of mobility and shorten hospitalization time. 19 Studies have reported that visual feedback training, which corrects subjective vertical sense the Canadian Journal of neurologiCal SCienCeS through visual input, is beneficial to control symptoms of pusher syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Standing, min/session 11 ± 7 No. of sessions in which external references were used 7.2 ± 1.9 (4)(5)(6)(7)(8)(9)(10) No. of sessions with cotherapy (2 therapists) 3.3 ± 1.8 (1)(2)(3)(4)(5)(6) Abbreviations: RAGT = robot-assisted gait training; min-max = minimummaximum; nR-PT = nonrobotic physiotherapy.…”
Section: Primary Outcome Measuresmentioning
confidence: 99%
“…4 The behavior affects 10% to 18% of patients in stroke rehabilitation and considerably hampers the therapy and prolongs the rehabilitation process. [5][6][7][8] Such patients are only half as efficient and effective in their rehabilitation outcome compared to patients with stroke without pusher behavior. 8 Consequently, innovative treatment approaches that effectively reduce pusher behavior are urgently needed.…”
mentioning
confidence: 99%
“…Davies (1985) reported a peculiar behavior in stroke patients termed"pusher syndrome", characterized by pushing strongly towards the hemiplegic side in all positions and resisting any physical attempt at passive correction of the posture to bring the weight toward or over the midline of the body. Pusher behavior (PB) is observed in about 10% to 15% of stroke patients with hemiparesis (Abe, Kondo, Oouchida, Suzukamo, Fujiwara, & Izumi, 2012;Krewer, Luther, Müller, & Koenig, 2013). The mechanisms underlying PB have been attributed to a dysfunction of vertical perception that leads to a postural reactive behavior (Karnath & Brotetz, 2003;Karnath, Ferber, & Dichgans, 2000;Pérennou et al, 2008;Saj, Honoré, Coello, & Rousseaux, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Lee et al (2013) suggested that somatosensory impairment did not have a correlation with PB. PB is considered a negative factor in a stroke patient's recovery time (Krewer, Luther, Müller, & Koenig, 2013). Babyar et al (2009) demonstrated that post-stroke "pusher patients" had less Functional Independence Measure (FIM) efficiency and more dependency at discharge compared to matched controls with equal functional limitations.…”
Section: Introductionmentioning
confidence: 99%